Islamic Education Management Strategies in Enhancing the Quality of Human Resources Based on Islamic Character - Ifrohan Ifrohan; Miftahur Rohman (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
Islamic education has a very important role in shaping human resources (HR) who are not only academically intelligent but also have Islamic character. This research aims to analyse the Islamic education management strategies implemented in improving the quality of Islamic character-based human resources. The main focus of this research is to identify the challenges and obstacles faced in the implementation of Islamic education management, as well as to develop an effective and adaptive strategy model in shaping quality human resources with strong Islamic character. The research method used is a qualitative approach with interviews and observations in several Islamic education institutions. The results showed that effective Islamic education management involves the integration of character-based curriculum, Islamic leadership, and innovation in the learning process. This research is expected to contribute in formulating better management strategies in the world of Islamic education in Indonesia, in order to produce competent, competitive, and noble generations in accordance with Islamic values.